Distribution and agglomeration of gold in arsenopyrite and pyrite. - Aylmore, Mark G. (Curtin University, 1995)
The form and location of gold in the structure of arsenopyrite and pyrite minerals, and the mechanisms for the mobility agglomeration of gold in arsenopyrite during thermal treatment, have been studied using a combination of Rietveld X-ray diffraction refinement, Convergent Beam Electron Diffraction (CBED) and Atomic Location by Channelling Enhanced Microanalysis. The basic structure of all the arsenopyrite compositions studies, has been shown to be monoclinic P2(subscript)1/c, regardless of the variation in stoichiometry. An increase in the arsenic to sulfur ratio in the natural arsenopyrites was found to be associated with an increase in unit cell dimensions accompanied by expansions within the iron-centred octahedra along the [101] direction of the monoclinic cell and concommitant contractions of the octahedra in the (101) plane. There was no obvious relationship between variation in stoichiometry and structure of arsenopyrite which could provide information as to possible substitution of gold in its structure. However, atomic displacements caused by twinning or disorder, may help to incorporate gold.The synthesis of auriferous arsenopyrites showed that gold has to be in an ionic form to be taken up in the structure. The form of the gold species affects the distribution of gold in the structure, being chemically zoned when derived from a dichloro complex and more evenly distributed when derived from a hydrosulfido complex. It is suggested that rapid crystallisation, with resultant displacement faults along the b-axis, may contribute to higher concentrations of gold in the natural arsenopyrite structure. Electron probe microanalysis showed a possible slight iron-deficiency in some of the auriferous arsenopyrite grains analysed. However, the errors in the analyses were too high to provide conclusive evidence of gold substitution in the iron sites, as has been proposed in the literature.Analyses of natural and synthetic pyrites showed no deviations in structural parameters which could indicate possible substitution of gold or other impurities within the structure.Electron channelling experiments showed that gold was located on the sulfur sites in pyrite. In arsenopyrite, there was some evidence for gold located on the iron sites, however, most gold was interstitial, probably situated between the octahedra. This location is probably facilitated by the presence of the displacement faults as observed by CBED in the synthetic auriferous arsenopyrite.Breakdown of arsenopyrite under thermal treatment was topotactic along its b-axis, which converts to the a-axis in the pyrrhotite structure, following a reconstruction mechanism based on the preferential removal of arsenic over sulfur. Gold was visually recorded exsolving from the arsenopyrite structure and agglomerating as liquid metal globules as the arsenopyrite was chemically altered during thermal treatment under the Transmission Electron Microscopy electron beam. Gold became mobile on the decomposition of arsenopyrite, but this was not observed until a temperature of approximately 470 degrees celsius was reached. Above the temperature both solid solution and particulate gold became mobile. The interaction of arsenic vapour and gold reduced the melting point of gold.The observations on the effects of arsenic residence time, and the relative mobility of solid solution and particulate gold during the thermal decomposition of auriferous arsenopyrite and pyrite, have significant implications for improved industrial extraction of gold from these minerals.